2022
DOI: 10.1039/d2qi01085b
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical performance of ligand-free CsPb2Br5 perovskites

Abstract: Herein, we have developed a method for the facile aqueous synthesis of ligand-free cesium lead halide perovskite nanoplatelets with pure CsPb2Br5. The ligand-free CsPb2Br5 nanoplatelets showed good environmental stability, green...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The absorption spectra of CdSe and CsPb 2 Br 5 were converted into Tauc plots to determine the optical band gap ( E g ) using the following Kubelka–Munk equation: 30 αhv = A ( hv − E g ) 2 where hv , α , and A represent the photon energy, absorption coefficient, and proportionality constant, respectively. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The absorption spectra of CdSe and CsPb 2 Br 5 were converted into Tauc plots to determine the optical band gap ( E g ) using the following Kubelka–Munk equation: 30 αhv = A ( hv − E g ) 2 where hv , α , and A represent the photon energy, absorption coefficient, and proportionality constant, respectively. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S5,† the optical band gaps of CdSe and CsPb 2 Br 5 were determined to be 1.96 eV and 3.45 eV, respectively, which are in good agreement with previous reports. 30,34 Based on the relationship between the conduction band edge ( E CB ), valence band edge ( E VB ), and band gap ( E g ): E VB = E CB + E g , E VB for CdSe and E CB for CsPb 2 Br 5 were determined to be 0.65 V and −2.15 V ( vs. NHE), respectively. So the energy band structures of the CdSe quantum dots and perovskite CsPb 2 Br 5 are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Recent studies have shown that aqueous solvents are effective in enhancing the crystal quality and grain size of CsPb 2 X 5 . 24,26 Regrettably, in prior research, the high supersaturation of precursors within aqueous solutions compromised the stability of the growth medium. This resulted in accelerated nuclei growth, consequently yielding numerous small single crystals.…”
mentioning
confidence: 99%